2019
DOI: 10.1245/s10434-019-07948-x
|View full text |Cite
|
Sign up to set email alerts
|

Increase in Utilization of Nipple-Sparing Mastectomy for Breast Cancer: Indications, Complications, and Oncologic Outcomes

Abstract: Background-Nipple-sparing mastectomy (NSM) is increasingly performed for invasive breast cancer. Growing evidence supporting NSM's oncologic safety has led to its widespread use and broadened indications. Here we examine indications, complications, and long-term outcomes of therapeutic NSM.Methods-From 2003-2016, women undergoing NSM for invasive cancer or ductal carcinoma in situ (DCIS) were identified from a prospectively maintained database. Patient and disease characteristics were compared by procedure yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
62
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 50 publications
1
62
0
Order By: Relevance
“…A single institution study by Wang et al 51 showed that while 16.5% of patients had some nipple ischemia, eschar, or necrosis, only 5.6% ultimately required reoperation to remove the nipple. Valero et al 18 similarly reported a low rate of nipple excision of 4.5%.…”
Section: Trouble Shootingmentioning
confidence: 96%
See 3 more Smart Citations
“…A single institution study by Wang et al 51 showed that while 16.5% of patients had some nipple ischemia, eschar, or necrosis, only 5.6% ultimately required reoperation to remove the nipple. Valero et al 18 similarly reported a low rate of nipple excision of 4.5%.…”
Section: Trouble Shootingmentioning
confidence: 96%
“…Garcia‐Etienne et al published the Memorial Sloan Kettering Cancer Center (MSKCC) indications for NSM in breast cancer patients in 2009, and these served as a guideline for many major institutions at the time; (a) no clinical involvement of the nipple areolar complex (NAC); (b) tumor size up to T2; (c) tumor‐to‐nipple distance of more than equal to 2 cm; (d) inflammatory breast cancer was a contraindication 8 . Ten years later, Valero et al 10 reported the current criteria for NSM at MSKCC which excluded only those with locally advanced breast cancer, extensive disease in the periphery of the breast, direct invasion of the nipple with cancer, and tumor‐to‐nipple distance of less than and equal to 1 cm.…”
Section: Indicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this issue of Annals of Surgical Oncology, Valero and colleagues review the outcomes of 449 women with breast cancer who underwent 770 NSMs at Memorial Sloan Kettering Cancer Center (MSKCC) from 2003 to 2016. 2 Of 467 therapeutic NSMs, 337 (72.2%) were for invasive cancer, 126 (27.0%) were for ductal carcinoma in situ (DCIS), and 4 (0.9%) were for phyllodes tumors. They excluded patients with locally advanced disease, disease B 1 cm from the nipple, direct nipple involvement, and those with extensive disease in the periphery of the breast (due to concerns about limited exposure).…”
mentioning
confidence: 99%